Natural products based crown ethers: synthesis and their anticancer potential. Issue 3 (4th March 2022) - Iqbal, Tahseen; Arshad, Nuzhat; Hashim, Jamshed; Ali, Syed Abid; Zehra, Binte; Ahmad, Malik Shoaib; Hassan, Nabila; Ullah, Arif; Hamid, Syeda Zehra; Isaac, Ibanga Okon
Abstract: Natural products based novel crown ethers have been prepared by employing biologically active natural structures including tetrahydroisoquinoline, chrysin and biochanin-A as the side arms. The resulting crown scaffolds were evaluated for their anticancer potential against two cancer cell lines i.e. NCI-H460 (non-small lung carcinoma), MCF-7 (breast adenocarcinoma). The comparative study showed that the addition of crown scaffold put marked effects on antiproliferative profile of parent natural precursors and is significant for lung carcinoma in particular. Biochanin-A derived crown ether showed three (03) folds higher antiproliferative activity (IC50 = 6.08 ± 0.07 µM) against lung carcinoma as compared to standard drug cisplatin (IC50 = 19.00 ± 1.24 µM). Cytotoxic trends for NIH-3T3 cell lines were also examined and found reduced as compared to parent natural structures. Hence, these findings could open a new pathway towards developing effective carcinostatic drugs. HIGHLIGHTS: Four natural products based novel crown ethers have been developed. Comparative antiproliferative screening of crown ethers and natural precursors. Addition of crown showed marked effects on anticancer profile of natural products. Crown formation is significant for lung carcinoma potential in particular. Biochanin-A derived crown ether found three folds more active than standard drug. Graphical Abstract: UF0001